Efficiency of some theories of drainage for tile drain spacing: II. Transient flow - de Albuquerque, Paulo Emílio Pereira; ferreira, Paulo Afonso; Loureiro, Blanor Torres; Bernardo, Salassier (Pesquisa Agropecuaria Brasileira, 1992)
Two typical low land sois, flooded with superficial water-table, (Eutrophic Aluvial soil, of clay-loam texture, called a mineral soil; and an association of a Dystrophic Humic-Gley with a Dystrophic Organic soil, of sandy-clay texture, called an organic soil) were used for estimating values of subsurface tile drain spacing utilizing some theories of drainage for transient (non-steady-state) flow: Glover, Tapp-Moody, Boussinesq-Schilfgaarde, Hammad and Bouwer-Schilfgaarde, from a physical laboratory model. The proper laboratory model was useful for obtaining saturated hydraulic conductivity and porosity drainable values from water-table measurements. The actual spacing drain (149.0 cm) in the model was compared with values computed from the theories. When the tile drain was in contact with the impermeable-layer, the Glover and Tapp-Moody theories were inefficient for any type of soil. In general, the order of preference of the theories was: Glover, Hammad, Tapp-Moody, Bouwer-Schilfgaarde and Boussinesq-Schilfgaarde, for the two types of sofs studied.